Pengaruh Jenis Pelarut pada Ekstraksi Daun Kumis Kucing (Orthosiphon stamineus Benth) terhadap Kadar Kalium - Janugraheni Prasetya Ningrum; Fitria Susilowati; Lija Oktya Artanti (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Indonesia has a variety of biological resources in various regions. One of the plants that can be used as medicine is Orthosiphon stamineus Benth. Orthosiphon stamineus Benth has several secondary metabolites, one of them is Potassium that has diuretic function. This study aims to know the effect of the solvent type to the level of Pottasium on the extraction of Orthosiphon stamineus Benth. The research method was done using atomic absorption spectrophotometry instrument. Samples were obtained and identified from UPT Materia Medica Batu Malang, East Java, sample was extracted by percolation method and infusion. The sample was the destructed then was destructied using HNO3 to transform organic metal into inorganic, then measured the absorbance using atomic absorption spectrophotometry at wavelength 766,5. The result showed that the concentration of potassium in Orthosiphon stamineus Benth in water solvent, ethanol 70%, ethanol 96%, and methanol were (29,256 ± 1,581) mg/L, (51,294 ± 5,028) mg/L, (31,406 ± 2.777) mg/L, (58.351 ± 2.925) mg/L. The method had in standard deviation value of each solvent is; water solvent 0,005, ethanol 70% 0,017, ethanol 96% 0,009, and methanol 0,001. Based on statistical test calculations using different test calculations over two samples there was a difference in average of Potassium level between each solvent, with the highest Potassium content found in methanol solvent.